Clinical Performance of CAD/CAM Monolithic Lithium Disilicate Implant‐Supported Single Crowns Using Solid or Predrilled Blocks in a Fully Digital Workflow: A Retrospective Cohort Study With Up To 33 Months of Follow Up. Issue 1 (27th April 2021) - Bompolaki, Despoina; Punj, Amit; Fellows, Christopher; Truong, Christina; Ferracane, Jack L.
Abstract: Purpose: To assess the clinical performance of CAD/CAM monolithic implant‐supported restorations manufactured using a fully digital workflow and two different types of ceramic blocks. Materials and Methods: One hundred and one patients received single‐unit implant‐supported restorations at a University predoctoral clinic. All restorations were designed and fabricated using either a predrilled LS2 block (group P, n = 59) or a conventional solid LS2 block with an occlusal opening drilled manually prior to crystallization (group M, n = 42). The mean follow‐up time after restoration delivery was 18.4 ± 4.8 months (range 12 to 33 months). Patients with less than a 12‐month follow‐up were excluded. Electronic health records were reviewed to identify number and type of complications during the follow‐up time. Clinical outcomes were classified as success, survival, and failure of the restoration. Chi‐square tests were used to identify differences in success and survival rates between the groups. Nonparametric Mann‐Whitney U tests were used to identify differences in the number of major and minor complications as well as the total number of complications that were observed among groups. Results: Overall success and survival rates were 80.2% and 97%, respectively. Seventy one restorations (70.3%) were complication‐free. There were no significant differences between the groups with regards to the number of complications or success and survival rates. Conclusions: Single‐unit CAD/CAM monolithic implant‐supported restorations that are fabricated in a fully digital workflow present relatively high complication rates and moderate short‐term clinical outcomes. Clinical studies with longer follow‐up times are needed to evaluate long‐term outcomes of these restorations.